2015
DOI: 10.1007/8904_2015_414
|View full text |Cite
|
Sign up to set email alerts
|

Bladder and Bowel Dysfunction Is Common in Both Men and Women with Mutation of the ABCD1 Gene for X-Linked Adrenoleukodystrophy

Abstract: Background: X-linked adrenoleukodystrophy (X-ALD) is a disorder caused by mutations in the ABCD1 gene. The commonest phenotype of X-ALD is adrenomyeloneuropathy (AMN), which is characterised by involvement of the spinal cord and peripheral nerves. The aim of this study was to evaluate bladder and bowel symptoms in men with AMN and female X-ALD carriers.Methods: In this cross-sectional study, patients with confirmed mutation of the ABCD1 gene attending a tertiary care service were approached about bladder and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
(46 reference statements)
0
8
0
5
Order By: Relevance
“…3 ). Thus, we reasoned that a predisposition for temporary, pronounced activation of monocytes seem to be associated with X-ALD and could possibly vary with disease course-related factors like microscopic dysmyelinative foci in AMN brain tissue or subclinical urinary tract infection due to bladder dysfunction ( Powers et al , 2000 ; Hofereiter et al , 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…3 ). Thus, we reasoned that a predisposition for temporary, pronounced activation of monocytes seem to be associated with X-ALD and could possibly vary with disease course-related factors like microscopic dysmyelinative foci in AMN brain tissue or subclinical urinary tract infection due to bladder dysfunction ( Powers et al , 2000 ; Hofereiter et al , 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, fecal incontinence was reported as an early symptom, even occurring in a few patients without signs of myelopathy on exam. The second study (n = 48) assessed symptoms in patients with AMN and reported that moderate to severe overactive bladder symptoms are highly prevalent, with symptoms being under-treated [ 12 ]. The majority of patients disclosed either no or “very minor” bowel symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord involvement is less in SCAs compared to Friedreich’s ataxia, and this could account for the lower prevalence of bowel complaints in our cohort. Other neurodegenerative diseases with myelopathy, such as X‐linked adrenoleukodystrophy 38 , present higher prevalence and severity of bowel complaints. The presence of a more widespread central nervous system involvement in these other complex disorders in comparison with SCA patients might account for this difference.…”
Section: Discussionmentioning
confidence: 99%